Effect of Infection by Beauveria bassiana and Metarhizium anisopliae on the Feeding of Uvarovistia zebra. Issue 1 (2nd July 2015) - Mohammadbeigi, A.; Port, G.
Abstract : To identify the susceptibility of long-horned grasshoppers to entomopathogenic fungi, the effect of infection with the fungi Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Clavicipitaceae) and Metarhizium anisopliae (Metchnikoff) Sorokin (Hypocreales: Clavicipitaceae) on food consumption by Uvarovistia zebra (Uvarov) (Orthoptera: Tettigoniidae) was investigated. Preliminary results showed that both fungi had a negative effect on food consumption of the insects. For both fungi a significant reduction of food consumption and faeces production by insects were observed between the highest spore concentration (5 × 10 6 spores/ml) and other treatments. Compared with control insects, the insects treated with 5 × 10 6 spores/ml of B. bassiana and M. anisopliae showed 60 and 63% reduction in mean food consumption/insect, respectively. The corrected cumulative percent mortality of the insects treated with the highest concentration of B. bassiana and M. anisopliae were 57.7 and 55.5%, respectively. This was the first account of these entomopathogenic fungi being used against a species from this family, therefore based on the results obtained from this research, it could be said that the fungi have pathogenicity effect on U. zebra as a long-horned grasshopper.